Teaching by principles - H Douglas Brown (Prentice-Hall, 1994)
The book synthesizes the accumulation of knowledge into a practical principles approach to teaching English as a second or foreign language. It consist of three parts: *) Part One: Foundations for classroom practice. *) Part Two: Contexts of teaching. *) Part Three: Designing anf implementing techniques